Preliminary Analysis of the Surgical Treatment of Anorectal Malformations in Russia - Morozov, Dmitry; Pimenova, Evgeniya; Oculov, Evgeniy; Gusev, Alexey; Utkina, Kseniya (European Journal of Pediatric Surgery, 2015)
The article provides the analysis of a survey of the professional community of Russian pediatric surgeons, dedicated to the treatment of anorectal malformations (ARM). The authors evaluated the differences and similarities in classification, surgical procedures, time of definitive repair, and postoperative management of ARM in different hospitals and centers. This was done by a survey upon specialists and experts in Russia followed by a symposium with live surgery, open discussion, and vote. Overall, 85% of the delegates supported the idea to create several regional centers of pediatric coloproctology as the way to improve the treatment of ARM in Russia. Moreover, 80% of delegates agreed to create a universal database of ARM information. The development of neonatal surgery and videoendoscopic surgical methods in the treatment of patients with ARM requires creation of a national guideline by the Russian Association of Pediatric Surgeons. Next step will concern standardization of the diagnosis and surgical treatment of children with ARM. This study is a collaborative effort to provide Russian Consensus on treatment of ARM.
Keywords: anorectal malformations; Russian consensus; pediatric coloproctology